An improved sum-of-sinusoids-based Rayleigh and Rician fading channel simulation model. (5th September 2019) - Sharma, Mohit; Dhanjal, Manpreet
Sum of Sinusoids has been considered as a common approach to model the Rayleigh as well as Rician fading channel in the multipath environment. Various models have been suggested by various authors as modifications of Clarke's model to best fit the theoretical results. In this paper, modification has been proposed on the angle of arrival of signal at receiver to address the situations where scatterers are scarcely present in the proximity of the receiver. Therefore, probability of reception of signal is assumed higher in ‒π/2 to +π/2 than in the rest of the range. The proposed model is a generalised model for Rayleigh and Rician channels adaptable to wide range of scenarios. Simulation results of proposed model in terms of autocorrelation function, probability density function and power spectral density function are in agreement with the reference Clarke's model.